Peran Badan Usaha Milik Desa dalam Pengembangan Objek Wisata Sumber Gempong di Desa Ketapanrame - Aisyah Aprilia Prasetyo; Sukmana, Hendra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this writing is to evaluate and explain the role of Village-Owned Enterprises in developing the Sumber Gempong tourist destination. The theoretical framework applied in this research includes three indicator components, namely motivation, encouragement, and dynamism. The results of the research show that the village government plays an important role in the development of the Sumber Gempong tourist attraction in Trawas sub-district, Mojokerto district, in accordance with established indicators. First, there is a motivator needed to ensure the sustainability of tourism businesses, and the role of Bumdes as a motivator involves encouraging the community to be active in managing these natural tourist attractions. Second, the government's role as a facilitator is achieved through providing a supportive environment for the community and implementing optimal development to improve regional development. Third, the government's role as a dynamist includes encouraging the community to participate in the development process and maintaining the dynamics of regional development.